Critical thinking skills and concepts mastery on the topic of temperature and heat - Jamaludin Jamaludin; Sulastri Kakaly; John Rafafy Batlolona (Intelektual Pustaka Media Utama, 2022)
This study aimed to determine the effect of the inquiry-discovery learning model on critical thinking skills and mastery of students' physics concepts on the topic of temperature and heat. This quasi-experimental research used posttest only control group design in which there are two groups in this design, each of which was selected randomly. The sample in this study was 34 students for the experimental class and 34 students for the control class. The results showed that there was a difference between inquiry-discovery learning and conventional learning in improving students' critical thinking skills and mastery of physics concepts. Inquiry-discovery learning affects critical thinking skills and students' mastery of physics concepts. Future research is expected to explore variables that can sharpen students' physics skills through inquiry-discovery learning.